Compliance level toward COVID-19 preventive measures and associated factors among the Ambo University community, 2021 - Roga, Ephrem Yohannes; Bekele, Gemechu Gelan; Gonfa, Dajane Negesse (Frontiers in Public Health, 2022)
Background: Coronavirus illness is a highly contagious viral infection with serious health consequences that has been happened all around the world. Application of COVID-19 prevention precautions with public health and social interventions by the general public are critical to successfully combating the epidemic. Therefore, this study was aimed to determine the level of compliance and associated factors with COVID-19 prevention strategies. Methods: A facility based cross-sectional study was conducted from June 01 to August 30, 2021 on a sample of 380 randomly selected Ambo university community. Self-administered structuralized questionnaire was used to collect the data. The determining factors with the level of compliance were finally identified using a multivariate logistic regression model. The association was reported using odds ratios with a 95% CI, and significance was declared using a P-value of less than 0.05. Results: A total 378 respondents participated in the study with a response rate of 98.9%. Most of the respondents, 75.7%, 57.9%, 47.4%, 61.9% had good knowledge, favorable attitude, good practice and good compliance towards COVID-19 preventive measures respectively. Participants with age between 18-30 [AOR= AOR=2.23, 95% CI: (1.13, 4.41)], good knowledge [AOR=2.64, 95% CI: (1.46, 4.78)], favorable attitude [AOR=4.5, 95% CI: (2.63, 7.71)], good practice [AOR=2.98, 95% CI: (1.82, 4.89)] were significantly associated with good compliance towards COVID-19 preventive measures respectively. Conclusion and Recommendation: Despite the fact that COVID-19 is a global and national priority, the preventive measures were not sufficiently followed. Therefore, it is essential to continue working on community’s knowledge, practices and attitude about COVID-19 preventive measures through media campaigns, which will ultimately increase compliance. Additionally, the concerned stakeholders should consider the required interventions for the strongly associated factors that have been discovered in this current study. Keywords: Compliance, COVID-19, knowledge, attitude, practice, Ambo university